URGENSI PENDIDIKAN KARAKTER BAGI PERKEMBANGAN ANAK USIA DINI DALAM PANDANGAN ISLAM - Susanti, Salamah Eka (JURNAL ISLAM NUSANTARA, 2021)
Education functions to form good character because good character is the initial capital for humans to realize a prosperous life. This study aims to provide an overview or description of the importance of instilling character education at an early age, especially for teachers and parents. This type of research is bibliographic research or library research. The research method used is descriptive-analytical. Based on the results of the study, it can be concluded: Character education in early childhood has four methods of character learning based on values and moral education, namely as follows: 1) learning methods for teaching values; 2) learning models based on the development of moral reasoning; 3) learning models for value analysis; 4) learning models for project citizens. In addition to these four methods, the role of a teacher or parent is vital to inform some daily behavior by the norms, ethics, or rules that have been applied.